Analisis Potensi Wisata Religi Di Kabupaten Banjar - Imam Suharto; RR. Yulianti Prihatiningrum; Claudia, Meiske; Rifani, Ahmad (Universitas Lambung Mangkurat, 2025)
This study uses a descriptive qualitative approach to achieve three objectives: (1) to evaluate how the distribution of religious tourism objects can be optimized as tourist destinations; (2) to evaluate the problems and challenges faced in the development of religious tourism objects; and (3) to make policy recommendations for the development of religious destination objects in Banjar Regency. The data collection method used was in-depth interviews with key subjects selected for this study. The results of the study explain that there are 18 religious destination locations in Banjar Regency consisting of the tombs of scholars. The absence of facilities and infrastructure, the lack of local resource contributions to the existence of tourist objects, and the lack of efforts to encourage religious-based tourism are some of the obstacles faced. Improvement and development of tourism facilities and infrastructure, strengthening the role of local resources, and intensifying the promotion of religious-based tourism are some of the strategic actions that can be taken to overcome these obstacles.